Habits of Spanish and European athletes on altitude training: Do all methods work equally well? - Campo Beamud, C.; Sancho Bielsa, F. J.; Rodrigo-Carranza, V. (Scientific Journal of Sport and Performance, 2026)
Objective: The training context of athletes from different locations can affect their altitude training camps. The aim of this study was to compare the habits of Spanish and European athletes during high altitude training camps. Methods: Descriptive analysis using questionnaires was conducted to investigate the altitude training practices of elite European athletes (n = 28) compared with Spanish athletes (n = 35). Moreover, all variables were assessed with an analysis of variance (ANOVA). Results: The most commonly method used by athletes was Live High - Train High (LHTH) . Most Spanish athletes train at altitudes above 2000m, while European athletes train at 1800m. The European athletes group usually compete 2-3 days after the camp, while the most Spanish athletes compete 3 weeks after the camp. In both groups, the feeling of improved performance after the camp was similar. Spanish athletes had higher feeling of fatigue and more sleep problems than European athletes during the training camp (p < .005) while the Europeans have a better feeling at the end of the camp. Conclusion: Spanish athletes had similar habits to those of athletes from the rest of Europe. The main differences between groups were that the feeling of fatigue at the end of the altitude periods and the sleep problems during the camp. These subjective feelings during the training camp may affect the fact that Spanish athletes preferred to compete up to three weeks after the camp while European athletes preferred to compete in the first 2-3 days after the camp.